2017
DOI: 10.1590/s1677-5538.ibju.2016.0078
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia for patients undergoing shockwave lithotripsy for urinary stones – a systematic review and meta-analysis

Abstract: Background Shock wave lithotripsy (SWL) is the first line treatment modality for a significant proportion of patients with upper urinary tracts stones. Simple analgesics, opioids and non-steroidal anti-inflammatory drugs (NSAIDs) are all suitable agents but the relative efficacy and tolerability of these agents is uncertain.Objectives To determine the efficacy of the different types of analgesics used for the control of pain during SWL for urinary stones.Materials and Methods We searched the Cochrane Renal Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
(129 reference statements)
0
15
0
Order By: Relevance
“…Akcali et al [18] concluded that lornoxicam, an NSAID, can be safely and efficiently preferred in pain control during SWL. In a recent meta-analysis that assessed analgesia for patients undergoing SWL, no significant difference in pain scores was reported between NSAIDs or opioids [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akcali et al [18] concluded that lornoxicam, an NSAID, can be safely and efficiently preferred in pain control during SWL. In a recent meta-analysis that assessed analgesia for patients undergoing SWL, no significant difference in pain scores was reported between NSAIDs or opioids [4].…”
Section: Discussionmentioning
confidence: 99%
“…Analgesics including paracetamol, nonsteroidal anti-inflammatory drugs (NSAIDs), and opioids have also been found to provide sufficient pain control during SWL. Nontraditional methods such as music, acupuncture, and transcutaneous electrical nerve stimulation have also been used [4].…”
Section: Introductionmentioning
confidence: 99%
“…More side effects would be anticipated from using opioids than simple analgesics or NSAIDs. [14,15]. Still, there is no consensus on the standard analgesic regimen for controlling pain during ESWL.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high intensity of pain that is applied by the first generation of lithotripters, ESWL required general or spinal-epidural anesthesia, but with the use of the new generation of the lithotripters that needs low energy for lithotripsy, we can use the topical and local methods such as oral medications and infiltration of local anesthetics and intravenous administration of sedative drugs for stone breaking. Therefore, ESWL has become an outpatient procedure ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to this method is to use of infusion pumps such as patient-controlled analgesia (PCA) device, with administering a bolus on demand, and low dose infusion plus bolus. It has been shown that PCA is superior to the bolus-only technique ( 7 , 8 ). Also, the successful use of target-controlled infusion (TCI) device for pain management in ESWL has been reported.…”
Section: Introductionmentioning
confidence: 99%